A thermostable organic solvent-tolerant lipase from Brevibacillus sp.: production and integrated downstream processing using an alcohol-salt-based aqueous two-phase system - Leykun, Senaite; Johansson, Eva; Vetukuri, Ramesh Raju; Ceresino, Elaine Berger; Gessesse, Amare (Frontiers in Microbiology, 2023)
Lipases are used for the synthesis of different compounds in the chemical, pharmaceutical, and food industries. Most of the reactions are carried out in non-aqueous media and often at elevated temperature, requiring the use of organic solvent-tolerant thermostable lipases. However, most known lipases are not stable in the presence of organic solvents and at elevated temperature. In this study, an organic solvent-tolerant thermostable lipase was obtained from Brevibacillus sp. SHI-160, a moderate thermophile isolated from a hot spring in the East African Rift Valley. The enzyme was optimally active at 65°C and retained over 90% of its activity after 1 h of incubation at 70°C. High lipase activity was measured in the pH range of 6.5 to 9.0 with an optimum pH of 8.5. The enzyme was stable in the presence of both polar and non-polar organic solvents. The stability of the enzyme in the presence of polar organic solvents allowed the development of an efficient downstream processing using an alcohol-salt-based aqueous two-phase system (ATPS). Thus, in the presence of 2% salt, over 98% of the enzyme partitioned to the alcohol phase. The ATPS-recovered enzyme was directly immobilized on a solid support through adsorption and successfully used to catalyze a transesterification reaction between paranitrophenyl palmitate and short-chain alcohols in non-aqueous media. This shows the potential of lipase SHI-160 to catalyze reactions in non-aqueous media for the synthesis of valuable compounds. The integrated approach developed for enzyme production and cheap and efficient downstream processing using ATPS could allow a significant reduction in enzyme production costs. The results also show the potential of extreme environments in the East African Rift Valley as sources of valuable microbial genetic resources for the isolation of novel lipases and other industrially important enzymes.